Conserved and distinct morphological aspects of the salivary glands of sand fly vectors of leishmaniasis: an anatomical and ultrastructural study - Nacif-Pimenta, Rafael; Pinto, Luciana C; Volfova, Vera; Volf, Petr; Pimenta, Paulo F P; Secundino, Nagila F C (Parasites & vectors, 2020)
BACKGROUND: Sand flies are vectors of Leishmania spp., the causative agents of leishmaniasis in vertebrates, including man. The sand fly saliva contains powerful pharmacologically active substances that prevent hemostasis and enhance Leishmania spp. infections. On the other hand, salivary proteins can protect vaccinated mice challenged with parasites. Therefore, sand fly salivary proteins are relevant for the epidemiology of leishmaniasis and can be a potential target for a vaccine against leishmaniasis. Despite this, studies on sand fly salivary glands (SGs) are limited. METHODS: The present study analyzes, in detail, the morphology, anatomy and ultrastructure of the SGs of sand fly vectors of the genera Lutzomyia and Phlebotomus. We used histology, transmission and scanning electron microscopy and lectin labeling associated with confocal laser microscopy. RESULTS: The SGs have conserved and distinct morphological aspects according to the distinct sand fly species. Each SG has a single rounded lobe constituting of c.100-120 secretory cells. The SG secretory cells, according to their ultrastructure and lectin binding, were classified into five different subpopulations, which may differ in secretory pathways. CONCLUSIONS: To the best of our knowledge, these morphological details of sand fly salivary glands are described for the first time. Further studies are necessary to better understand the role of these different cell types and better relate them with the production and secretion of the saliva substances, which has a fundamental role in the interaction of the sand fly vectors with Leishmania.
Keywords: Ultrastructure; Leishmaniasis; Animals; Disease Vectors; Sand fly vectors; Lectin binding; infekce přenášené vektorem; Mosquito Vectors; Phlebotomus; leishmanióza; zvířata; slinné žlázy; Secretory cell population; Microscopy, Electron; Salivary Glands; Psychodidae; komáří přenašeči; elektronová mikroskopie